SIMILARITIES BETWEEN DADA KORKUT STORIES AND UZBEK FOLK EPICS (Conferencea, 2024)
In this article, the classification of Dada Korkut’s stories and the occurrence of the events described in it in other sagas, the fact that one event can be based on several sources and that everything ends well in the end, are emphasized in this article.